2014
DOI: 10.1159/000362538
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolism as a Cause of Renal Artery Occlusion and Acute Kidney Injury: The Recovery of Kidney Function after Two Weeks

Abstract: Thromboembolic occlusion is a rare cause of acute kidney injury (AKI). It may lead to permanent loss of renal function. Our patient, who had dilated cardiomyopathy and prosthetic aortic valve, presented with AKI due to thromboembolic arterial occlusion of a solitary functioning kidney. After 2 weeks delay, local intra-arterial thrombolytic treatment with recombinant tissue plasminogen activator was performed without sufficient effect. However, a subsequent percutaneous transluminal angioplasty with stenting wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…However, there are case reports about the recovery of kidney function even after weeks of total occlusion 17. In another report, recovery of renal functions was seen with renal artery stenting done after 2 weeks of thromboembolic occlusion of renal artery 18. Another report showed unsuccessful outcome after renal artery stenting, done after 7 days of symptom onset in the transplanted kidney 19.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are case reports about the recovery of kidney function even after weeks of total occlusion 17. In another report, recovery of renal functions was seen with renal artery stenting done after 2 weeks of thromboembolic occlusion of renal artery 18. Another report showed unsuccessful outcome after renal artery stenting, done after 7 days of symptom onset in the transplanted kidney 19.…”
Section: Discussionmentioning
confidence: 99%
“…The main cause of acute renal infarction is reported to be atrial fibrillation [ 12 , 13 ], with approximately 2 percent of the patients being predisposed to have a renal thromboembolic event during the natural history of the disease [ 14 ]. Dilated cardiomyopathy [ 4 , 5 , 15 ], infective endocarditis, or thrombi of atheroma from the suprarenal aorta [ 1 ] are other potential sources of emboli to a renal artery. Nevertheless, a retrospective study of 94 patients identified arterial thrombosis secondary to blunt abdominal trauma as being the major cause for renal infarction (30,8%) [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Full recovery of kidney function has been estimated to occur if a revascularization method is undertaken in the first 60 to 90 minutes after a complete artery occlusion; otherwise irreversible renal damage takes place [ 4 ]. However, cases of almost full recovery can be seen even when the treatment is delayed by 10–14 days because of a misdiagnosis [ 5 ]. This can be explained by the existence of either a collateral artery supplying the kidney or an incomplete occlusion, the cases with total artery occlusion being even rarer than the diagnosis itself.…”
Section: Introductionmentioning
confidence: 99%
“… 6 On the other hand, percutaneous endovascular therapies have been reported to be worthwhile, with some studies showing clear benefit with a delay of several days 2 , 7 or even weeks. 8 , 9 Nevertheless, poor outcomes with early intervention have also been reported, 1 making the therapeutic window still unclear, especially because the literature is scarce. Moreover, regardless of successful reperfusion, renal function does not improve consistently.…”
Section: Discussionmentioning
confidence: 99%